The Price of Delay and the Uncoupling of Severity: A Penalized Multivariate Analysis of Treatment Adequacy Versus Timing as Determinants of Congenital Syphilis - Ida Ayu Sintya Pratiwi; I Wayan Dharma Artana (HM Publisher, 2026)
Background: Despite global elimination targets, congenital syphilis (CS) remains a critical cause of preventable neonatal morbidity. While the importance of antenatal screening is established, the relative impact of treatment adequacy (dosage/adherence) versus timing on neonatal severity—specifically the uncoupling phenomenon where severe visceral damage occurs despite normal birth biometrics—remains under-characterized in resource-limited settings. Methods: A retrospective cross-sectional study analyzed 101 syphilis-exposed mother-infant pairs at a tertiary referral center in Indonesia (2021–2025). We evaluated maternal serologic testing time, treatment timing, and treatment adequacy (defined strictly per CDC guidelines; inadequate defined as <30 days pre-delivery, non-penicillin, or missed doses). To address sparse data bias and quasi-complete separation in the dataset, Firth’s Penalized Likelihood Logistic Regression was utilized to calculate adjusted odds ratios (aOR) for severe clinical manifestations. Results: The prevalence of proven/possible CS was 58.4%. High-fidelity analysis revealed that inadequate maternal treatment was the dominant predictor of adverse outcomes (aOR = 85.40; 95% CI: 14.2–512.5; p<0.001), significantly outpacing delayed serologic testing (aOR = 4.8; p=0.012). A distinct uncoupling profile was identified: neonates born to inadequately treated mothers had high odds of severe visceral manifestations (hepatosplenomegaly, hematological failure) (aOR = 11.05), yet traditional biometrics (low birth weight, prematurity) showed no significant association (p>0.05). Conclusion: Treatment adequacy is the single most critical determinant of neonatal prognosis. The dissociation between normal birth weight and severe organ damage suggests that anthropometry is a poor triage tool for syphilis. A zero-tolerance policy for therapeutic deviations is imperative.